2020
DOI: 10.1155/2020/8393724
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Day-to-Day Route-Choice Behavior: Evaluating the Effect of ATIS Market Penetration

Abstract: This paper examines the travelers’ day-to-day route-choice behavior with Advanced Traveler Information Systems (ATIS) through laboratory-like experimental method. Five groups of route-choice behavior experiments are designed to simulate actual daily behavior of travelers. In the experiment, subjects are provided with different levels of the complete road network information to simulate the proportion of subjects equipped with ATIS equipment (i.e., ATIS market penetration) and choose the routes repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Zhou et al and Liu et al have mainly discussed the impact of traffic information publishing on the overall urban day-to-day travel system under different penetration rates of ATIS; their conclusion has shown that it is not that the higher the popularity of ATIS, the better. When its market penetration rate is 75%, the least fluctuation in traffic flow can be achieved, and the macro road network can also reach the most stable state [109,110]. Rahimi-Farahani et al have studied different strategies for traffic information publishing using the route guidance system (RGS), such as minimizing the total travel time of travelers or minimizing the total route length of travelers.…”
Section: Dialectical Discussion Of Traffic Information On Micro Trave...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al and Liu et al have mainly discussed the impact of traffic information publishing on the overall urban day-to-day travel system under different penetration rates of ATIS; their conclusion has shown that it is not that the higher the popularity of ATIS, the better. When its market penetration rate is 75%, the least fluctuation in traffic flow can be achieved, and the macro road network can also reach the most stable state [109,110]. Rahimi-Farahani et al have studied different strategies for traffic information publishing using the route guidance system (RGS), such as minimizing the total travel time of travelers or minimizing the total route length of travelers.…”
Section: Dialectical Discussion Of Traffic Information On Micro Trave...mentioning
confidence: 99%
“…Improve urban transportation conditions [76][77][78] Willing to accept information prompts [79-81] Provide travel decision-making assistance [35,[82][83][84][85] Willing to face risk with the help of information [86] Reduce emissions, protect environment [83] Information provided by mobile devices affects most [87] Negative Bad effects of improper information dissemination [88] Unwilling to accept information prompts [89][90][91][92][93][94] Real road network information may not lead to best traffic distribution [95] Information prompts do not lead to traffic condition improvement [96] A majority of travelers are indifferent to information prompts [97-99] Better to follow intuition than follow information prompts [100] Neutral Interaction in social platforms is also a part of travel information [101,102] Different attitudes towards information prompts [103][104][105][106] Information prompts may not always have a fixed effect [107,108] Effectiveness varies depending on the penetration rate of ATIS [109,110] Information dissemination has different strategies [111] Differentiated information dissemination considering different personalities of receivers [112] Correct and incorrect information may both have good effects [113] Different impact of information prompts inside/outside congestion area [114] 3.…”
Section: Positivementioning
confidence: 99%
“…Their findings suggest that the most efficient information structure is to provide real-time information rather than foregone-payoff information. Liu et al (2020) evaluate the impact of different proportions of users having complete network information about route choice behavior in a three-route Braess network. There are two types of players in their setting: players that observe the complete route choice distribution for all of the previous periods and players who only possess information about their chosen routes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of specific behavioral traits of travelers on the evolution of network states have also been modeled within a day-to-day dynamic framework [18]. Parallel to the stream of studies addressing the theoretical aspects of day-to-day traffic dynamics, an active area of research dealing with the empirical analysis of repeated route choice behavior in real or simulated settings has developed [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%